Impact of changing life style on age of menarche - Upadhyay, Kritika; Dhok, Archana; Jaiswal, Arpita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Menarche marks the beginning of the reproductive phase in a woman’s life or the onset of puberty Menarche is said to be early when it begins before the age of 8 years in a girl’s life. Early menarche can turn up into many consequences. This can only be controlled by carefully exploring and analyzing the factors causing early menarche. This study aims to assess the impact of changing lifestyle on age of menarche. Methods: It is a prospective cross-sectional study, included 112 subjects in group I (girls had their menarche at the age of <11 years) and 88 subjects in group II (Girls had their menarche at the age between 12-14 years). A self-made questionnaire was used for collecting the data. Results: It is found that 80.32% girls from group I and 47.73% girls from group II consume junk food daily or 2-3 times per week. 66.07% girls from group I and 51.14% girls from group II play indoor games daily or 2-3 times per week. 52.86% girls from group I and 26.14% girls from group II go to hotel once a week and 57.14% girls from group I and 73.86% girls from group II go to hotel occasionally. Conclusions: Girls who are not much interested in playing outdoor games, more frequently go to hotel, eat more junk food and consume more amount of fats in the daily home-made food have a significant lowering in the age of menarche.